HISTORY OF LATIN LANGUAGE AND TEACHING TECHNOLOGY - Suyundikov Nigmatullo Sagdullayevich (Journals Park Publishing, 2024)
This article traces the evolution of Latin language education, highlighting traditional pedagogy and the integration of technology. It discusses ancient methods, medieval preservation efforts, and modern digital innovations, emphasizing the enduring relevance of Latin.
Keywords: Latin language, rich tapestry of Latin language, ancient Rome, ancient pedagogy, medieval monasteries and scholasticism.